DIAGNOSTIC AND PROGNOSTIC SIGNIFICANCE OF GENETIC MARKERS OF MOTOR NEURON DISEASE. (Multidisciplinary Journal of Science and Technology, 2026)
Genetic studies have significantly expanded the understanding of motor neuron disease and related motor neuron damage. Currently, the TARDBP, SOD1, and FUS genes are listed as the main genetic determinants most associated with the disease, and some sources include mutations in the IL-6 and TBK1 genes involved in the regulation of inflammatory processes among the important genes that cause severe neurodegenerative changes. The existence of interpopulation differences indicates the need to study genetic factors separately in different regions.